Efficacy of percutaneous microwave ablation guided by contrast-enhanced and two-dimensional ultrasound for in hepatic alveolar echinococcosis in difficult/dangerous locations - Huang, Wangxing; Hu, Zhipeng; Qi, Lina; Zhang, Xiaoyan; Li, Min; Yu, Mingan; Hua, Guoyong (Frontiers in Medicine, 2024)
Background Ultrasound-guided microwave ablation (MWA) has become a popular method for treating malignant liver tumors. However, few studies have investigated its use in the treatment of hepatoalveolar echinococcosis (HAE). This study aimed to explore the effectiveness and safety of contrast-enhanced ultrasound combined with two-dimensional ultrasound-guided MWA for the treatment of HAE in difficult/dangerous locations. Methods Data from 81 patients, who were diagnosed with hepatic alveolar hydatid disease in difficult/dangerous locations between January 2018 and January 2023, and underwent contrast-enhanced ultrasonography combined with two-dimensional ultrasound-guided MWA, were analyzed. After undergoing MWA, patients were followed up to determine whether the lesions recurred and to evaluate the therapeutic effect of MWA. Preoperatively, individualized strategies were designed for lesions in different locations, and different auxiliary ablation technologies were used for contrast-enhanced ultrasound combined with two-dimensional ultrasound-guided MWA to achieve complete inactivation of lesions in difficult/dangerous locations. Results MWA was performed on 89 HAE lesions in 81 patients. The median diameter of the lesions was 2.86 cm (interquartile range [IQR] 2.36–3.49 cm). The complete ablation rate after surgery was 100%, with a recurrence rate of 11.11%, and median follow-up of 24 months (IQR 12–48 months). The incidence of minor complications was 14.81%; no serious complications or deaths occurred. Compared with before surgery, TB, DB, alanine aminotransferase, and aspartate aminotransferase levels increased (p < 0.001), albumin platelets and activated partial thromboplastin time decreased (p < 0.05), with no statistical difference in prothrombin time (p > 0.05). Conclusion MWA may be a safe and effective method for treating HAE in difficult/dangerous locations, and may represent a new and alternative option for this patient population.